PEMBUATAN GAME RUNAWAY FROM CULIK DENGAN ALGORITMA FUZZY MAMDANI - Krisdiawan, Rio Andriyat; Rohmana, Muhamad Faza; Permana, Aji (TI S1 FKOM UNIKU, 2020)
The game comes from an English word that has the basic meaning of the game. Games have a type or can be called a genre, the function of the game genre is used to classify a game based on how the interaction of the game. Endless runner is a genre in the game. Endless runner games generally have a game system where players must avoid an obstacle and get as many scores as possible. At this time many games are endless runners, but there are no endless runner games with a kidnapper theme and a speed system that uses algorithms. Mamdani fuzzy algorithm is a Fuzzy inference method for rules represented in the form of If-Then where the system output is not a Fuzzy set but a constant or linear equation. In this study, the Mamdani fuzzy algorithm is applied to the conditions at which obstacles appear. With the Mamdani fuzzy algorithm a speed system can be made. In making games a game development method is also needed, so that the stages of development are clearer and as expected. For this research, the game development method used is the Game Development Life Cycle (GDLC) development model. GDLC is a game development process that adopts an iterative approach consisting of 6 development phases, starting from the initialization / concept making phase, preproduction, production, Testing (Alpha testing, Beta testing), and realease. From the 6 phases it can be grouped into 3 main processes, namely: Initialization Process which consists of concepts and designs, Production process consists of Pre Production, Production, and Testing consisting of Alpha Testing and Beta Testing, the last is Realease.Keywords: Games, Endless runner, Fuzzy Mamdani Algorithm, Game Development Life Cycle (GDLC).